PENGURUSAN ORGANISASI DARI PERSPEKTIF ISLAM: SATU KAJIAN KES DI PERBADANAN JOHOR DAN SAPURA HOLDINGS - Basir, Siti Arni (Jurnal Syariah, 2019)
The article is an attempt to review the principles of management according to Islamic perspective. It tries to explain the importance of Islamic principles for organizational performance and productivity.